The expansion of small-scale drug dealing structures and the call to think up the community: an approach to Naranjo's case - Rojas Lizano, Marco (2019)
In the context of a series of transformations that have been occurring in the Western Region of Costa Rica (Occidente) and the increase of violence causedby gangs linked to drug trafficking, this article analyses the expansion of drug dealing from the Greater Metropolitan Area towards Naranjo canton, which has generated a territoriality through necropower. Achille Mbembe’s analyticalproposal on necropolitics allows a reading of the subjective impact and theplace of this drug trade when it comes to thinking about the conformation of the community.